Siosar Village Community Socio-Economic Role In Regional Development Efforts - Herijon Lingga, Osland; Sirojulizam, Sirojulizam; Purwoko, Agus; Siddik Thoha, Achmad (International Journal of Economics and Management, 2023)
Regional development planning isaimed at achieving harmony and balance in development between regions in accordance with their natural potential and utilizing this potential in an efficient, orderly and safe manner. The purpose of this study was to see the role of socio-economic impacts on the planning of the Siosar tourism village area. This research method is a quantitative study by testing the hypothesis of the socio-economic influence of the community on regional planning in Siosar Village, Karo Regency. By involving 559 samples of family heads to be distributed research questionnaires and data processing using SEM-PLS. The results of the study stated that there is a Socio-Economic influence of the community (X) on Regional Development (Y) because it has a P value of 0.009 which is smaller than the significant level of 0.05.